Phenotype-Genotype analysis of caucasian patients with high risk of osteoarthritis - Wang, Yanfei; Chyr, Jacqueline; Kim, Pora; Zhao, Weiling; Zhou, Xiaobo (Frontiers in Genetics, 2022)
Osteoarthritis is a common cause of disability and pain around the world. Epidemiologic studies of family history have revealed evidence of genetic influence on osteoarthritis (OA). Although many efforts have been devoted to exploring genetic biomarkers, the mechanism behind this complex disease remains unclear. The identified genetic risk variants only explain a small proportion of the disease phenotype. Traditional GWAS focuses on radiographic evidence of OA and excludes sex chromosome information in the analysis. However, the prevalence of comorbidities among patients with OA is high, indicating multiple diseases share a similar genetic susceptibility with OA. Furthermore, gender differences in OA are multifactorial, with a higher frequency in women, indicating that the X chromosome plays an essential role in OA pathology. In this study, we performed GWAS of OA and OA-associated key comorbidities on 3366 OA patients from the Osteoarthritis Initiative (OAI). To investigate the genetic association of OA with comorbidities, we calculated the genetic correlation coefficients between OA and common human diseases using publicly available summary statistics to identify whether they share a similar mechanism. We performed Mendelian randomization to further identify the possible causal relationship between OA and OA-related clinical features. We identified four novel genetic risk loci associated with knee OA. A significant OA-associated locus rs5933886 was identified by X chromosome-wide association analysis. By calculating the LD score, we found positive correlations between OA and heart disease and stroke. A strong genetic correlation was observed between knee OA and inflammatory disease, including eczema, multiple sclerosis, and Crohn’s disease. Our study suggested that knee alignment was one of the major risk factors in OA development, and we also found knee pain was not a causative factor of OA although it was the most common symptom of OA. We investigated several significant positive and negative genetic correlations between OA and common chronic diseases, suggesting substantial genetic overlapping of OA on these traits. The X-chromosome association analysis supports the necessary role of the X chromosome in future studies.